Rancang Bangun Antena Mikrostrip Mimo 2×2 Square Patch U-Slot Untuk Komunikasi 5g Frekuensi 2,3 GHz - Handayani, Esti; K N, nurwijayanti (Universitas Dirgantara Marsekal Suryadarma, 2025)
The 2.3 GHz frequency band is one of the recommended spectrums for 5G deployment due to its favorable propagation characteristics and capability to support high data throughput. However, microstrip antennas operating in this band often suffer from limited bandwidth and radiation efficiency. This research aims to design and implement a 2×2 MIMO microstrip antenna using a square patch with a U-slot and an inset-feed technique to enhance bandwidth and radiation performance for 5G applications. The initial antenna dimensions were calculated using standard microstrip theory, followed by modeling and optimization using CST Microwave Studio Suite 2019. The optimized antenna was then fabricated and tested using a Vector Network Analyzer (VNA) and radiation pattern measurements. Experimental results show that the antenna operates around 2.3 GHz with bandwidth values ranging from 61 to 65 MHz, VSWR below 1.2, and an axial ratio of 1.23 dB, indicating circular polarization. Additionally, the measured gain reaches 6.98 dB. These results demonstrate that the U-slot modification combined with inset-feed implementation effectively improves antenna performance, making the design suitable for MIMO systems in 5G networks.